Statistical sciences - Jaworski, John; Gallen, Anne-Marie (Milton Keynes : Open University Worldwide)
Explanation on how to do the statistical sciences
Copy available in DVD format
Keywords: Ecology -- Simulation methods; Ecology -- Research